From Novice to Master(s) Level Athlete: A Longitudinal Analysis of Psychological Changes in a Marathon Runner Completing 119 Marathons - Xiuxia Liu; Lisheng Huang; Shunying Lin (Behavioral Sciences, 2025)
Long-term participation in marathon running involves complex psychological processes, yet existing research predominantly focuses on static, single-time-point analyses. This study addresses the gap by longitudinally examining the psychological evolution of an elite Chinese marathon runner (119 marathons completed) to uncover dynamic shifts from novice to master(s) level athlete stages. A longitudinal single-case study was conducted using inductive thematic analysis. Data included in-depth interviews, observational records, and archival materials spanning three life stages (youth, middle age, maturity). Five experts validated the credibility and validity of the findings. The results show that the runner’s psychological trajectory followed a three-phase model: competitive drive (youth: external achievement motivation), reflective transformation (middle age: health prioritization and identity reconfiguration), and value reconstruction (maturity: legacy mission and lifelong running). These stages were shaped by the interplay of achievement motivation, social roles, and physiological changes. Notably, the transition mirrored China’s marathon culture shift from elitism to mass participation. This study proposes a novel “motivation-physicality-society” interaction model, challenging static theories of sports psychology. It highlights how long-term runners dynamically balance extrinsic and intrinsic motivations while embedding personal growth within socio-cultural transformations. The findings offer theoretical foundations for optimizing psychological support systems and promoting sustainable marathon engagement.